2005
DOI: 10.1111/j.1447-073x.2005.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and histology of Virchow's node

Abstract: A regional lymphatic system is composed of the first, second, third and even fourth or much more intercalated nodes along the lymptatic route from the periphery to the venous angle or the thoracic duct. The third or fourth node is usually termed the last-intercalated node or end node along the route. Similarly, one of the supraclavicular nodes is known to correspond to the end node along the thoracic duct. It is generally called 'Virchow's node', in which the famous 'Virchow's metastasis' of advanced gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…The end node of the thoracic duct is the so-called Virchow node and is located near or at this jugulo-subclavian venous junction. 25 The involvement of the Virchow node by metastasis can be seen in several types of cancer. Viacava and Pack investigated 4365 patients suffering from abdominal and thoracic tumors and found an enlarged Virchow node in 2.8% of the patients.…”
Section: The Virchow Nodementioning
confidence: 99%
See 1 more Smart Citation
“…The end node of the thoracic duct is the so-called Virchow node and is located near or at this jugulo-subclavian venous junction. 25 The involvement of the Virchow node by metastasis can be seen in several types of cancer. Viacava and Pack investigated 4365 patients suffering from abdominal and thoracic tumors and found an enlarged Virchow node in 2.8% of the patients.…”
Section: The Virchow Nodementioning
confidence: 99%
“…More specifically, in 2005, Mizutani et al found that the thoracic duct is divided into 3-10 several collateral ducts and these ducts surround the Virchow node. 25 …”
Section: The Virchow Nodementioning
confidence: 99%
“…LSCLN collects lymph through the thoracic duct and from most areas of the body. In contrast, RSCLN takes its supply mainly from the mediastinum, lungs, and esophagus [1]; in a patient with OC, the route of ILNR in LSCLN is lymphatic dissemination, and that in RSCLN is lymphatic dissemination from the transcoelomic spread site. In the present case, although the diagnosis of ILNR was surgically confirmed, the suspected presence of a peritoneal lesion was based on PET/CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…A finding of an enlarged node has been regarded as strongly indicative of the presence of cancer in the abdomen. In contrast, right supraclavicular lymph node (RSCLN) takes its supply mainly from the mediastinum, lungs, and esophagus [1]. We report a case of recurrent OC presenting with an isolated RSCLN metastasis with no evidence of any other recurrent part after 52 months from initial surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This is the junction where incoming lymph is introduced back into venous circulation through the left subclavian vein. An enlarged Virchow node is referred to as the Troisier sign, and is highly suggestive of abdominal malignancy 4. Supraclavicular lymph nodes are a common location for metastasis from lung, gastric, and esophageal cancers, and their presence may contraindicate surgical management of these diseases 5…”
Section: Introductionmentioning
confidence: 99%